Non-targeting control for MISSION shRNA library silences SNRPD3 leading to cell death or permanent growth arrest - Maria Czarnek; Katarzyna Sarad; Agnieszka Karaś; Jakub Kochan; Joanna Bereta (Elsevier, 2021)
In parallel with the expansion of RNA interference (RNAi) techniques, accumulating evidence indicates that RNAi analyses might be seriously biased due to the off-target effects of gene-specific short hairpin RNAs (shRNAs). Our findings indicated that off-target effects of non-targeting shRNA comprise another source of misinterpreted shRNA-based data. We found that SHC016, which is one of two non-targeting shRNA controls for the MISSION (commercialized TRC) library, exerts deleterious effects that lead to elimination of the shRNA-coding cassette from the genomes of cultured murine and human cells. Here, we used a lentiviral vector with inducible SHC016 expression to confirm that this shRNA induces apoptosis in murine cells and senescence or mitotic catastrophe depending on the p53 status in human tumor cells. We identified the core spliceosomal protein, small nuclear ribonucleoprotein Sm D3 (SNRPD3), as a major SHC016 target in several cell lines and confirmed that CRISPRi knockdown of SNRPD3 mimics the effects of SHC016 expression in A549 and U251 cells. The overexpression of SNRPD3 rescued U251 cells from SHC016-induced mitotic catastrophe. Our findings disqualified non-targeting SHC016 shRNA and added a new premise to the discussion about the sources of uncertainty in RNAi results.